Multimodal Interactive Continuous Scoring of Subjective 3D Video Quality of Experience - Taewan Kim; Jiwoo Kang; Sanghoon Lee; Bovik, Alan C. (IEEE transactions on multimedia, 2014)
People experience a variety of 3D visual programs, such as 3D cinema, 3D TV and 3D games, making it necessary to deploy reliable methodologies for predicting each viewer's subjective experience. We propose a new methodology that we call multimodal interactive continuous scoring of quality (MICSQ). MICSQ is composed of a device interaction process between the 3D display and a separate device (PC, tablet, etc.) used as an assessment tool, and a human interaction process between the subject(s) and the separate device. The scoring process is multimodal, using aural and tactile cues to help engage and focus the subject(s) on their tasks by enhancing neuroplasticity. Recorded human responses to 3D visualizations obtained via MICSQ correlate highly with measurements of spatial and temporal activity in the 3D video content. We have also found that 3D quality of experience (QoE) assessment results obtained using MICSQ are more reliable over a wide dynamic range of content than obtained by the conventional single stimulus continuous quality evaluation (SSCQE) protocol. Moreover, the wireless device interaction process makes it possible for multiple subjects to assess 3D QoE simultaneously in a large space such as a movie theater, at different viewing angles and distances. We conducted a series of interesting 3D experiments showing the accuracy and versatility of the new system, while yielding new findings on visual comfort in terms of disparity, motion and an interesting relation between the naturalness and depth of field (DOF) of a stereo camera.